Bioethics from a pragmatic perspective: ethical issues in biopharmaceuticals - Fournel, Michael A. (Acta Bioethica, 2005)
In recent times competitive, commercial and fiscal pressures have introduced new and challenging issues for the pharmaceutical industry. This essay identifies some of these issues and proposes mechanisms for their resolution. This overview is not intended to serve as a comprehensive assessment, but rather as an introduction to and call for utilization of bioethics as a tool in the resolution of practical issues that otherwise could limit the development and introduction of important therapeutic entities into the clinic.